Strengthening Qur’anic Memorization through Muraja’ah and Tasmi’ at Daarul Khoir Islamic Boarding School, Bogor - Luthfiah, Salwaa; Syarif, Fajar (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study examines how Murāja’ah (systematic revision) and Tasmī’ (recitation assessment) are implemented to support Qur’anic memorization among santri at Daarul Khoir Islamic Boarding School, Gunung Sindur, Bogor. Using a qualitative descriptive approach, data were collected through observations, semi-structured interviews, and document review of tahfidz records and schedules. Participants were selected purposively and included the pesantren leader, musyrifah, tahfidz teachers, selected santri, and one parent representative. The findings indicate that structured Murāja’ah helps santri maintain memorization continuity by improving recitation fluency and reducing errors in tajwīd and makhraj through routine rehearsal. Tasmī’ functions as a formative assessment mechanism that provides immediate correction, strengthens preparedness for examinations, and encourages disciplined learning routines. Document review also shows that the tahfidz program applies semester-based targets and differentiated guidance for santri who require additional support. Thus, the integration of Murāja’ah and Tasmī’ contributes to a more organized memorization culture and reinforces learning discipline within the pesantren context. Abstrak Penelitian ini mengkaji bagaimana metode Murāja’ah (pengulangan terstruktur) dan Tasmī’ (setoran/evaluasi bacaan) diterapkan untuk mendukung kualitas hafalan Al-Qur’an santri di Pondok Pesantren Daarul Khoir Gunung Sindur, Kabupaten Bogor. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui observasi, wawancara semi-terstruktur, serta telaah dokumen (jadwal, catatan setoran, dan arsip program tahfidz). Informan dipilih secara purposive meliputi pengasuh pesantren, musyrifah, guru tahfidz, santri terpilih, serta satu perwakilan wali santri. Hasil penelitian menunjukkan bahwa Murāja’ah yang dijadwalkan membantu menjaga kesinambungan hafalan melalui peningkatan kelancaran bacaan dan pengurangan kesalahan tajwid dan makhraj karena latihan yang berulang dan terpantau. Sementara itu, Tasmī’ berfungsi sebagai evaluasi formatif melalui koreksi langsung, penguatan kesiapan ujian, serta pembiasaan disiplin belajar. Telaah dokumen juga menunjukkan adanya target semesteran dan mekanisme pendampingan bagi santri yang memerlukan penguatan. Secara keseluruhan, integrasi Murāja’ah dan Tasmī’ mendukung terbentuknya budaya menghafal yang lebih teratur dan disiplin di lingkungan pesantren.